Petri Nets-based method to elicit component-interaction related safety requirements in safety-critical systems. (October 2018) - Zhu, Danjiang; Tan, Huobin; Yao, Shuzhen
Abstract: System component-interaction has been critical for system safety, accompanied by the ever-growing complexity of safety-critical systems. As a novel causality model, Systems-Theoretic Accident Modeling and Process (STAMP) has been well used to obtain component-interaction related safety requirements. However, the original process model used in STAMP can't specify component-interactions clearly, which limits the component-interaction related requirement elicitation. Petri nets, which are effective tools to model complex systems, can help analyze component-interactions and make the safety requirement elicitation with STAMP effectively. This paper extends traditional Petri Nets, Control Logical Petri Net (CLPN), to model and analyze component-interactions in the control process. Then four kinds of basic dysfunctional interactions that can lead to system hazards are described with CLPN. Additionally, several rules are listed to guide dysfunctional interactions analysis with CLPN. Based on the studies above, an integrated approach eliciting safety requirement is proposed. The experimental results illustrate the feasibility and availability.